Development of Virus-Like Particles (VLPs) for Hepatitis C Virus genotype 4: a novel approach for vaccine development in Egypt - Ahmed A. Ali; Rasha A. M. Azouz; Nahla A. Hussein; Reem El-Shenawy; Naiera M. Helmy; Yasmine S. El-Abd; Ashraf A. Tabll (BMC Biotechnology)
Abstract Background Egypt has the highest global prevalence of Hepatitis C Virus (HCV) infection, particularly of genotype 4. The development of a prophylactic vaccine remains crucial for HCV eradication, yet no such vaccine currently exists due to the vaccine development challenges. The ability of Virus-Like Particles (VLPs) to mimic the native virus and incorporate neutralizing and conformational epitopes, while effectively engaging both humoral and cellular immune responses, makes them a promising approach to addressing the challenges in HCV vaccine development. Methods Lentiviral-based vectors were constructed and employed to integrate the full-length sequence of Core, E1, E2, and P7 genes of HCV genotype 4 into the genome of Human Embryonic Kidney cells (HEK293T). Upon the expression, HCV structural proteins can oligomerize and self-assemble into VLPs mimicking the structure of HCV native virus. VLPs were purified and characterized for the development of a potential VLPs-based vaccine. Results In this study, mammalian cells were successfully engineered to stably express HCV structural proteins and generate non-infectious VLPs for HCV genotype 4. The expression of HCV-integrated genes resulted in a successful production of HCV structural proteins, which oligomerized and self-assembled into two layers enveloped VLPs. Electron microscopy analysis of purified VLPs revealed spherical particles with an average diameter of 60–65 nm, closely resembling mature HCV virions. These results highlighted the potential of these VLPs as a vaccine candidate for HCV genotype 4. Conclusions HCV genotype 4 remains an underexplored target in vaccine development, despite its significant public health burden, especially in Egypt. The successful generation of VLPs for this genotype represents a promising avenue for further vaccine development. The established system provides a robust platform for the production and study of VLP-based vaccines targeting HCV genotype 4.